PENGARUH STRATEGI PEMBELAJARAN KREATIF PRODUKTIF TERHADAP MOTIVASI BERWIRAUSAHA MAHASISWA DI UNIVSERSITAS PGRI PALEMBANG - Lestari, Neta Dian (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The purpose of the study to know the effect of productive creative learning strategies on student entrepreneur motivation education programs a k un tansi FKIP University PGRI Palembang. Creative productive in question is the learning process of educators should be able to grow productive thinking habits , which is characterized by growing a critical attitude, creative and independent in thinking and learning by : a). fostering the ability to think and learn regularly, b) cultivate a critical attitude in thinking and c) cultivate a creative attitude in thinking and learning , Creative productive in 30 icon kuliner of Palembang. The research data was obtained from the respondents as many as 30 students. Data collection is done by direct observation, questionnaire and documentation. The results showed that there is a significant influence between productive creative learning strategies on student entrepreneurship motivation student study program a k un tansi FKIP University PGRI Palembang. The results showed t count = 9,13 3 ≥ t table = 1,701, then accept H a and reject H o which reads no effect of productive creative learning strategy toward entrepreneurship motivation student accounting education education program FKIP University PGRI Palembang that is equal to 74% while the rest 26% are influenced by other factors. Keywords— Learning strategy, creative productive, motivation